Value Orientations From the World Values Survey: How Comparable Are They Cross-Nationally?. (July 2016) - Alemán, José; Woods, Dwayne
We examine data from the World Values Survey regarding the existence of two consistent orientations in mass values, traditional versus secular/rational and survival versus self-expression. We also evaluate the empirical validity of Welzel's revised value orientations: secular and emancipative. Over the years, a large body of work has presumed the stability and comparability of these value orientations across time and space. Our findings uncover little evidence of the existence of traditional–secular/rational or survival–self-expression values. Welzel's two dimensions of value orientations—secular and emancipative—seem more reflective of latent value orientations in mass publics but are still imperfectly capturing these orientations. More importantly, these value orientations do not seem very comparable except among a small number of advanced post-industrial democracies. We call attention to the use of value measurements to explain important macro-level phenomena.